Diagnosis of canine leptospirosis: evaluation of two PCR assays in comparison with the microagglutination test = Diagnóstico de leptospirose canina: avaliação de dois ensaios de PCR em comparação com o teste de microaglutinação - Martin, Paula L.; Stanchi, Nestor O.; Brihuega, Bibiana Felicitas; Bonzo, Estela; Galli, Lucía; Arauz, María S. (Colegio Brasileiro de Patologia Animal, 2019)
Canine leptospirosis is definitely diagnosed by demonstrating seroconversion in paired serum samples from the acute and convalescent period by the microagglutination test (MAT). However, the application of a polymerase chain reaction (PCR) assay can provide earlier confirmation of suspected cases. The objective of this study was to evaluate two PCR assays used in diagnosis of human leptospirosis (lipL32 real-time PCR and rrs conventional PCR) in cultured microorganisms and experimentally contaminated samples (whole blood, serum, urine), and investigate their applicability in clinical samples from dogs with presumptive diagnosis of leptospirosis by using the MAT as a reference. The analytical sensitivity of the lipL32 real-time PCR was 1 genome equivalent per reaction, whereas that for the rrs conventional PCR was 10 genome equivalents per reaction. Both assays amplified the pathogenic strains but were negative when evaluating the DNA of other microorganisms that may be present in clinical samples. The lipL32 real-time PCR detected 100 bacteria/mL in whole blood samples, 1000 bacteria/mL in serum samples and 10 bacteria/mL in urine samples, whereas the rrs conventional PCR detected 1000 bacteria/mL in whole blood and serum samples and 100 bacteria/mL in urine samples. Seven out of the 51 samples from dogs with presumptive diagnosis of leptospirosis were considered as confirmed cases. ThelipL32 real-time PCR detected positive results in six of the seven confirmed cases, whereas the rrs conventional PCR detected four. The PCR assays evaluated proved to be useful diagnostic tools in the confirmation of canine leptospirosis when used together with the MAT.